Authenticity and Transformation: Existential Philosophy’s Contributions to Lifelong Learning - Adrienne Johnson (Adult Education Research Conference, 2013)
Existential philosophy contributes richly to the study of lifelong learning. To expose the depths of this conviction, I will explore how the concepts of authenticity and transformation help clarify and actually bolster the role of existential philosophy in lifelong learning.